Public television: oblique review of scientific literature in Spanish. Handcrafted bibliometrics. - Arango Lopera, Carlos Andrés (2024)
In the current era, discussing television and the public sphere entails grappling with at least two anachronisms. While television, as traditionally understood, undergoes a profound transformation in its production and consumption models, the concept of the public sphere is beset by numerous threats and concerns. Against this backdrop, inquiring about public television, and more specifically, about scientific production in this field, might seem like an exercise in futility. However, now more than ever, it is pertinent to examine the progress of knowledge production in this domain, as academic contributions can undoubtedly shed light on the future of both television and the public sphere. This article thus reviews scientific works on public television written in Spanish between 2010 and 2023, compiled from the Scopus database, with the aim of probing the questions, methodologies, and scientific contributions made in the Spanish language. The methodology blends bibliometric analysis with narrative state-of-the-art reviews. This combination seeks to understand the field’s dynamics through critical metrics while scrutinizing the exercise of questioning public television from a qualitative and critical perspective.